The Innate Immune Response of Atlantic Salmon (Salmo salar) Is Not Negatively Affected by High Temperature and Moderate Hypoxia - Zanuzzo, Fábio S.; Beemelmanns, Anne; Hall, Jennifer R.; Rise, Matthew L.; Gamperl, Anthony K. (Frontiers in Immunology, 2020)
Climate change is predicted to increase water temperatures and decrease oxygen levels in freshwater and marine environments, however, there is conflicting information regarding the extent to which these conditions may impact the immune defenses of fish. In this study, Atlantic salmon were exposed to: 1) normoxia (100-110% air saturation) at 12oC; 2) an incremental temperature increase (1oC per week from 12 to 20oC), and then held at 20oC for an additional 4 weeks; and 3) ‘2’ with the addition of moderate hypoxia (~65-75% air saturation). These conditions realistically reflect what farmed salmon in some locations are currently facing, and future conditions in Atlantic Canada and Europe, during the summer months. The salmon were sampled for the measurement of head kidney constitutive anti-bacterial and anti-viral transcript expression levels, and blood parameters of humoral immune function. Thereafter, they were injected with either the multi-valent vaccine Forte V II (contains both bacterial and viral antigens) or PBS (phosphate-buffer-saline), and the head kidney and blood of these fish were sampled at 6, 12, 24 and 48 h post-injection (HPI). Our results showed that: 1) neither high temperature, nor high temperature + moderate hypoxia, adversely affected respiratory burst, complement activity or lysozyme concentration; 2) the constitutive transcript expression levels of the anti-bacterial genes il1β, il8-a, cox2, hamp-a, stlr5-a and irf7-b were up-regulated by high temperature; 3) while high temperature hastened the peak in transcript expression levels of most anti-bacterial genes by 6 – 12 hours following V II injection, it did not affect the magnitude of changes in transcript expression; 4) anti-viral (viperin-b, mx-b and isg15-a) transcript expression levels were either unaffected, or downregulated, by acclimation temperature or V II injection over the 48 HPI; and 5) hypoxia, in addition to high temperature, did not impact immune transcript expression. In conclusion, temperatures up to 20°C, and moderate hypoxia, do not impair the capacity of the Atlantic salmon’s innate immune system to respond to bacterial antigens. These findings are surprising, and highlight the salmon’s capacity to mount robust innate immune responses (i.e., similar to control fish under optimal conditions) under conditions approaching their upper thermal limit.